Penanganan Abses Periapikal Kronis Palatal Anterior pada Gigi Insisif Lateral Rahang Atas - Skolastika Piscasari Sukoutoro Atmojo; Atia Nurul Sidiqa (Jurnal Material Kedokteran Gigi, 2021)
Chronic periapical abscess is an advanced suppurative lesion from the acute phase, originating from the inflammation of necrotic pulp tissue, and is accompanied by symptoms of pain that have subsided, and can return to the acute phase if the etiologic factor is not eliminated. A 24-year-old female patient came to RSGM Unjani with a complaint of a pus-filled lump that irritates the palate of anterior teeth, feeling uncomfortable when chewing on her right upper anterior tooth since 3 weeks ago. The patient had been treated but the complaints did not improve. This case report shows that the administration of penicillin and metronidazole antibiotics which are used together as a combination of antibiotics is considered effective in suppressing the bacteria that cause suppurative inflammation.